2011
DOI: 10.3109/13693786.2010.531772
|View full text |Cite
|
Sign up to set email alerts
|

Toll like receptor 5 (TLR5) may be involved in the immunological response toAspergillus fumigatus in vitro

Abstract: Toll-like receptors (TLRs) are involved in the host defense against Aspergillus fumigatus infections, and some TLRs may even be exploited by the mould to escape immune mechanisms. We have previously shown that conidia from A. fumigatus increase expression of TLR5 in human monocytes. When further investigating a possible role of TLR5 in A. fumigatus infections, we observed a decrease in conidial viability after culturing with TLR5-knockdown THP-1 monocytes. Secondly, our experiments showed an increase in conidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 15 publications
0
18
0
1
Order By: Relevance
“…Spores, crude aqueous extracts, and/or isolated single components including various β‐glucans and proteases from A. fumigatus have been used in most of the studies published on immune responses following exposure to mold . Studies elucidating effects of viable spores or hyphae vs inactivated spores from A. fumigatus have reported that the growth stage (hyphae) and swelling spores have stronger pro‐inflammatory potential than inactivated spores . In the present study, we have systematically characterized spore and hyphae fragment preparations from four species common in indoor environments and compared their pro‐inflammatory potentials in different experimental models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spores, crude aqueous extracts, and/or isolated single components including various β‐glucans and proteases from A. fumigatus have been used in most of the studies published on immune responses following exposure to mold . Studies elucidating effects of viable spores or hyphae vs inactivated spores from A. fumigatus have reported that the growth stage (hyphae) and swelling spores have stronger pro‐inflammatory potential than inactivated spores . In the present study, we have systematically characterized spore and hyphae fragment preparations from four species common in indoor environments and compared their pro‐inflammatory potentials in different experimental models.…”
Section: Discussionmentioning
confidence: 99%
“…In general, TLR2 and TLR4 are considered to be key recognition components for host innate defense system against fungi . TLR5 has been reported to be involved in the immunological response to A. fumigatus in THP‐1 monocytes, and TLR9 in response to S. chartarum . PARs‐2 are a G protein‐coupled receptor that can be activated by proteases produced by molds .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, polymorphisms in TLR3 increase the risk of IA after hematopoietic stem cell transplantation, with these individuals demonstrating impaired IFN-1 and CD8 T cell responses to A. fumigatus RNA [27] . Regarding TLR5, although the A. fumigatus ligand putatively recognized by TLR5 is not known, in vitro genetic knockdown studies implicated a role for TLR5 in A. fumigatus killing [28] . Subsequently, a TLR5 stop single-nucleotide polymorphism (SNP) was identified as an independent risk factor for IA in recipients after allogenic hematopoietic stem cell transplantation [29] .…”
Section: Membrane-bound and Soluble Receptorsmentioning
confidence: 99%
“…The A. fumigatus stimulated release of these inflammatory cytokines is dependent on the expression of functional pattern recognition receptors such as TLR2, TLR4, TLR5 and TLR9 molecules (Braedel et al 2004;Meier et al 2003;Netea et al 2003;Rødland et al 2010), Dectin-1 (LeibundGutLandmann et al 2007Werner et al 2009), and MBL (Brummer and Stevens 2010). The lower production of these cytokines observed here in MIF-deficient mice might depend on a particular signaling pathway, as macrophages derived from MIF −/− mice have an impaired TLR4 signaling pathway (Roger et al 2001).…”
Section: Discussionmentioning
confidence: 56%